Depletion of microglia exacerbates postischemic inflammation and brain injury. Issue 6 (June 2017) - Jin, Wei-Na; Shi, Samuel Xiang-Yu; Li, Zhiguo; Li, Minshu; Wood, Kristofer; Gonzales, Rayna J; Liu, Qiang
Brain ischemia elicits microglial activation and microglia survival depend on signaling through colony-stimulating factor 1 receptor (CSF1R). Although depletion of microglia has been linked to worse stroke outcomes, it remains unclear to what extent and by what mechanisms activated microglia influence ischemia-induced inflammation and injury in the brain. Using a mouse model of transient focal cerebral ischemia and reperfusion, we demonstrated that depletion of microglia via administration of the dual CSF1R/c-Kit inhibitor PLX3397 exacerbates neurodeficits and brain infarction. Depletion of microglia augmented the production of inflammatory mediators, leukocyte infiltration, and cell death during brain ischemia. Of note, microglial depletion-induced exacerbation of stroke severity did not solely depend on lymphocytes and monocytes. Importantly, depletion of microglia dramatically augmented the production of inflammatory mediators by astrocytes after brain ischemia . In vitro studies reveal that microglia restricted ischemia-induced astrocyte response and provided neuroprotective effects. Our findings suggest that neuroprotective effects of microglia may result, in part, from its inhibitory action on astrocyte response after ischemia.